DISKUSI TENTANG PAHAM NORMATIF DAN TEOLOGIS LITURGI DALAM GEREJA KATOLIK - Pondaag, Stenly Vianny; Wuritimur, Amrosius (Department of Theology - Sekolah Tinggi Filsafat Seminari Pineleng, 2026)
This paper examines the development of the concept of liturgy in the Catholic Church by analyzing the relationship between its normative and theological dimensions. Using a literature review methodology, the study traces a paradigm shift from a predominantly normative understanding of liturgy toward a more explicitly theological interpretation. The normative concept understands liturgy primarily as a set of officially regulated, communal ritual actions through which the Church offers worship to God; this perspective was formally articulated in the Codex Iuris Canonici. In contrast, the theological understanding, which emerged through the liturgical movement and was articulated authoritatively in the encyclical Mediator Dei, conceives liturgy as the salvific action of Christ carried out in and through His Church. This theological paradigm finds its conciliar expression in Sacrosanctum Concilium and is further reinforced by the apostolic letter Desiderio Desideravi, particularly through its emphasis on the celebration of the Paschal Mystery as the heart of the liturgy. The paper argues that this theological emphasis does not replace or marginalize the normative dimension. Rather, subsequent canonical legislation rearticulates theological insights within juridical formulations, integrating both interior participation and external ritual order. The study concludes that the normative and theological concepts of liturgy are not mutually exclusive but must be understood as complementary and interdependent within Catholic liturgical theology and practice.